Perubahan Teknologi dan Efisiensi pada Organisasi Pengelola Zakat di Indonesia - Aam Slamet Rusydiana (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2018)
Zakah institution is the intermediary organizations based on social. Although based on social activities, but the management is still needs to uphold professional, accountability and transparency principles. This study attempts to analyze the productivity level of zakat organization in Indonesia, both in terms of changes of its efficiency, and also its technological. There are two things that are calculated in Malmquist index measurement that is catch-up effect and frontier shift effect. The catch-up effect measures the rate of change in relative efficiency from period 1 to period 2. Meanwhile the frontier shift effect measures the rate of technological change that is a combination of input and output from period 1 to period 2. The frontier shift effect is often called an innovation effect. Findings from the results of the productivity index analysis are very interesting. In general, there has been an increase in the level of productivity of zakat institutions in Indonesia in the period 2011 to 2016. The increase in productivity growth (1.116) of zakat institutions in Indonesia is generally caused by technological change (1.137) instead of changes in efficiency (0.982). Thus the service of zakat institutions is needed which is more innovative in relation to the development of technology in the future.